Malaria vaccine research: lessons from 2008/9. (August 2009) - Haque, Ashraful; Good, Michael F
Vaccination remains a crucial component of any initiative to control or eradicate malaria. With increasing reports of insecticide resistance in mosquitoes, and malaria parasite resistance to first-line drugs, it is clear that the development of an effective malaria vaccine is an urgent requirement for the improvement of global human health. This article highlights malaria vaccine research-related discoveries from 2008/9 to suggest that the time is now ripe for researchers to develop malaria vaccines that target many antigens from multiple stages of the parasite''s lifecycle. We also call for greater bidirectional information transfer between preclinical and clinical trials, to facilitate more efficient improvement of malaria vaccine candidates.